Opportunities and challenges of internal brain drain on national development: A focus on ICT lecturers on two selected higher institutions of learning in Zambia - Natalia Zulu; simon Banda; Betty Shitima Bweupe; Muoli Ngulube; judith Lubasi ziwa; John Pamba (Piramida Akademi, 2025)
This study investigated the opportunities and challenges of internal brain drain among ICT lecturers at two selected Zambian higher education institutions. Zambia's higher education sector, critical for national development, faces the persistent challenge of brain drain, which significantly disturbs its capacity for research and knowledge generation. Grounded in Equity Theory and Herzberg's Two-Factor Theory, the research utilized an embedded correlational mixed-methods design to understand factors influencing lecturers' retention and evaluate the impact of brain drain on institutional research output. The quantitative component involved a survey of 44 ICT lecturers selected via simple and systematic random sampling, with the sample size determined using Yamane's formula. The qualitative component, employing snowball sampling, included interviews with 7 departed lecturers. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically. Results indicated that economic disparities, including inadequate salaries and limited research funding, are primary drivers of emigration. The study identified negative consequences such as diminished research productivity and a decline in qualified faculty. It recommends a comprehensive, multi-pronged strategy to address retention through improved compensation, enhanced resource allocation, and clearer career progression pathways. Ultimately, this research provides a data-driven basis for retaining academic talent and contributes to the realization of the African Union's Agenda 2063, particularly its aspirations for inclusive growth and people-driven development.